PENGARUH KEBIJAKAN DIVIDEN DAN KEPUTUSAN INVESTASI TERHADAP NILAI PERUSAHAAN DENGAN STRUKTUR MODAL SEBAGAI VARIABEL INTERVENING (STUDI PADA PERUSAHAAN SUB SEKTOR BATU BARA YANG TERDAFTAR DI BEI PERIODE 2019–2024) - Sora Krisnanda Sari; Sri Hasnawati (Yayasan Nusantara Hasana Berdikari, 2026)
This study is designed to explore the impact of dividend distribution policies and investment choices on company value, with capital structure serving as an intervening variable, specifically in coal subsector companies listed on the Indonesia Stock Exchange during the 2019–2024 period. A quantitative approach is employed, utilizing secondary data collected from the companies' annual financial reports. The sample comprises 23 companies selected through purposive sampling. Data analysis was conducted using EViews software version 13, encompassing descriptive statistics, classical assumption tests, panel data regression, model selection, hypothesis testing, Sobel tests, and path analysis. The findings reveal that dividend policy has no significant influence on company value, as measured by the Dividend Payout Ratio (DPR). Conversely, investment decisions exhibit a negative impact on company value, proxied by Total Asset Growth (TAG). Capital structure, represented by the Long-term Debt to Equity Ratio (LDER), contributes positively to company value. Furthermore, capital structure fails to mediate the relationship between dividend policy and company value but successfully mediates the influence of investment decisions on company value.